Field guide to the common mangroves, seagrasses and algae of the Philippines - Calumpong, Hilconida P. (Makati City : Bookmark, 2007)
The diversity of plants in the coastal environment of the Philippines is one of the richest in the world.
vii. Acknowledgements -- 1. Introduction -- 2. About the Philippines -- 3. Mangroves -- 4. Seagrasses -- 5. Green Algae -- 6. Brown Algae -- 7. Red Algae -- References -- Glossary -- Index to Common Names -- Taxonomic Index.
Includes index.
Keywords: BIOTIC COMMUNITIES -- PHILIPPINES; SEAGRASSES; MARINE ALGAE; MARINE PLANTS -- PHILIPPINES